Anti-Inflammatory Effects and Mechanisms of Dandelion in RAW264.7 Macrophages and Zebrafish Larvae - Li, Wenju; Luo, Fulong; Wu, Xiaohui; Fan, Bei; Yang, Mingran; Zhong, Wu; Guan, Dongyan; Wang, Fengzhong; Wang, Qiong (Frontiers in Pharmacology, 2022)
Dandelions (Taraxacum spp.) play an important role in the treatment of inflammatory diseases. In this study, we investigated the anti-inflammatory effects of Dandelion Extract (DE) in LPS-induced RAW264.7 macrophages and copper sulfate (CuSO4)-induced zebrafish larvae. DE was not toxic to RAW264.7 cells at 75 μg/ml as measured by cell viability, and DE inhibited LPS-induced cell morphological changes as measured by inverted microscopy. In survival experiments, DE at 25 μg/ml had no toxicity to zebrafish larvae. By using an enzymatic standard assay, DE reduced the production of nitric oxide (NO) in LPS-induced RAW264.7 cells. Fluorescence microscopy results show that DE reduced LPS-induced ROS production and apoptosis in RAW264.7 cells. DE also inhibited CuSO4-induced ROS production and neutrophil aggregation in zebrafish larvae. The results of flow cytometry show that DE alleviated the LPS-induced cell cycle arrest. In LPS-induced RAW264.7 cells, RT-PCR revealed that DE decreased the expression of M1 phenotypic genes iNOS, IL-6, and IL-1β while increasing the expression of M2 phenotypic genes IL-10 and CD206. Furthermore, in CuSO4-induced zebrafish larvae, DE reduced the expression of iNOS, TNF-α, IL-6, and IL-10. The findings suggest that DE reduces the LPS-induced inflammatory response in RAW264.7 cells by regulating polarization and apoptosis. DE also reduces the CuSO4-induced inflammatory response in zebrafish larvae.